Subsurface Spatial Planning for Energy and Storage Applications in Germany - SME Annual Meeting 2025 - Malte J. M Gurgel (Society for Mining, Metallurgy & Exploration, 2025)
Subsurface spatial planning is becoming increasingly important in view of competing underground applications. This development is influenced by global agreements to reduce greenhouse gas emissions. Therefore, precise knowledge of the underground space is a basic prerequisite for future applications. The three-dimensional registration and reliable georeferencing of underground infrastructures can establish a holistic geodata basis for such tasks. Those tasks are discussed both for the development of energy projects such as deep geothermal energy as well as for storage applications. Research on geothermal energy has been carried out at RWTH Aachen University as part of the SuperC project in a license field in the Aachen area since 2001. Recently, this research has been extended to include monitoring aspects in the overlapping GEObservatorium Aachen field. The documentation and visualization of underground activities using photogrammetric methods like Structure from Motion is discussed based on recent research in sites for the final disposal of radioactive waste. Finally, both applications provide an outlook on supporting underground projects by using high-resolution geodata.